2016
DOI: 10.1016/j.jhealeco.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Earmarking and the political support of fat taxes

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…However, our result of a larger effect from a health and earmarked tax frame would be consistent with other studies suggesting that earmarking SSB taxes could make the tax more effective at reducing the demand for SSBs. Yet the social welfare implications depend on whether the reduction in SSBs consumption translates into actual healthcare cost savings and how those as well as tax revenue are allocated (Cremer et al, 2016). We also found that the greatest response to a 20% price increase among those who did not support a tax was when the health objective and earmarking of the tax was underlined, indicating that efforts to explain the tax purpose and investing proceeds into relevant cause may increase its objectives among the most sceptical.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…However, our result of a larger effect from a health and earmarked tax frame would be consistent with other studies suggesting that earmarking SSB taxes could make the tax more effective at reducing the demand for SSBs. Yet the social welfare implications depend on whether the reduction in SSBs consumption translates into actual healthcare cost savings and how those as well as tax revenue are allocated (Cremer et al, 2016). We also found that the greatest response to a 20% price increase among those who did not support a tax was when the health objective and earmarking of the tax was underlined, indicating that efforts to explain the tax purpose and investing proceeds into relevant cause may increase its objectives among the most sceptical.…”
Section: Discussionmentioning
confidence: 82%
“…A recent meta-analysis estimated that public support for SSB tax increases from 42% to 66% if revenues are used for health initiatives (Eykelenboom et al, 2019). In fact, Cremer, Goulao, and Roeder (2016) demonstrate, in a theoretical framework, that earmarking a fraction of tax proceeds to reduce health insurance premiums and retaining revenues to subsidise healthier goods can be welfare maximising (Cremer et al, 2016). Another recent study provided suggestive evidence of the potential effect of framing and information on earmaking tax revenue for health from Berkeley, California, where a penny-per-ounce tax on SSBs was introduced in 2015, with its revenues to be used for nutritional or other public health programs.…”
Section: Introductionmentioning
confidence: 99%
“…The basic argument is made by O' Donoghue andRabin (2003, 2006). Extensions can be found, for example, in Kotakorpi (2011, 2016), Cremer et al (2012Cremer et al ( , 2016. In contrast to our analysis, all these studies assume monotonically increasing instead of U-shaped health costs.…”
Section: Introductionmentioning
confidence: 80%
“…A possible explanation for the excess consumption of unhealthy goods is that individuals misperceive the adverse health effects of these goods in the long run. Alternatively, individuals may be subject to problems of self-control in their consumption (see, among others, Gruber and Koszegi, 2004; O'Donoghue and Rabin, 2006; Kotakorpi, 2008;Haavio and Kotakorpi, 2011;Cremer et al, 2012 andCremer et al, 2016). In either case, individuals make their consumption decisions according to a "perceived" or short-run utility function, which does not fully account for the long-run harmful impact of these goods on their health.…”
Section: Introductionmentioning
confidence: 99%